The Use of Integrated Learning Media of TikTok and Instagram Social Media on Student Learning Motivation on Cation Qualitative Analysis Materials Groups I and II - Hayuni Retno Widarti; Munzil Munzil; Neena Zakia; Deni Ainur Rokhim; Afis Baghiz Syafruddin; Zalfa Adhya Rachmanita (JCER (Journal of Chemistry Education Research), 2023)
This study was conducted to determine the effect of using integrated learning media TikTok and Instagram in increasing students' learning motivation in qualitative analysis materials for groups I and II. The research method used is descriptive qualitative research method using a distributed questionnaire to determine the increase in students' learning motivation. This research was conducted in one of the State Vocational High Schools in Malang City which involved 29 students of class XII Analytical Chemistry 1. Data analysis was in the form of a qualitative test on students' learning motivation. The results of the study indicate that the use of TikTok and Instagram learning media can increase students' motivation to study qualitative analysis materials for groups I and II. The existence of integrated learning media for TikTok and Instagram social media, allows students to learn material anytime and anywhere.